Collective working agreement between Independent Oil Workers' Union of Aruba and Lago Oil & Transport Co. Ltd. executed August 26, 1970 (IOWUA, 1970)
Ook odt.: Combenio colectivo di trabao entre Union Independiente di Trahadorna Petrolero di Aruba y Lago Oil & Transport Co. Ltd.